Determinan Entrepreneurial Spirit pada Pelaku Usaha di Sektor Digital - Leonita, Tracy; Kempa, Sesilya; Indriyani, Ratih (Universitas Negeri Surabaya, 2024)
This research aims to examine how income expectations and the social environment influence entrepreneurial spirit through the self-efficacy of Indonesian entrepreneurs operating in the digital business sector using a quantitative approach. This research involved 161 entrepreneurs using a purposive sampling technique. This research uses SEM-PLS data analysis techniques to prove allegations. The research results show that entrepreneurs need self-confidence in their ability to run a digital business to keep them enthusiastic about becoming an entrepreneurs. Apart from that, income expectations and social environment also determine the entrepreneurial spirit of an entrepreneur.